STRATEGI CONTENT MARKETING TERHADAP MINAT BELI KRIPIK KACA MR SNACK PADAAPLIKASI TIKTOK SHOP - Mutaqien, Nazzar; Roisah, Riris (Jurnal Ekonomi Manajemen, 2024)
This research aims to answer how Content marketing affects buying interest in customers to determine their buyinginterest. A quantitative method was used in this study, by collecting data through a survey using Google Form which was given to 100 respondents who used TikTok Shop including students, civil servants, employees, etc. in West Java. Respondents were selected using a non-random snowball sample. The results of the study show that content marketing is influential significant positive on Buying Interest in Customers who use TikTok Shop This result shows that the better the Content marketing, the higher the interest in buying Mr. Glass Chips, snacks.